An Investigation into Secondary School’s Approach to Collaboration and Communication with their Feeder Primary Schools - Lowe, Helen (STER, 2019)
This article focuses on the management of information transfer from primary to secondary school on all incoming first years. The research investigates how secondary schools use data on new students to inform teaching and learning specifically the data collected from the Education Passport.
Journal Article
Keywords: Research Subject Categories::SOCIAL SCIENCES; Post Primary Education; Transition; Collaboration; Education Passport; STER